Mental Health Screening for University Students in the Special Region of Yogyakarta - Fardhiasih Dwi Astuti; M. Junaidy Heriyanto; Widea Rossi Desvita; Rokhmayanti Rokhmayanti; Siti Kurnia Widi Hastuti; Budi Barata Kusuma Utami; Arlina Azka (Journal of Epidemiology and Public Health, 2024)
Background: Mental health disorders occur a lot among students. Failure to overcome mental health conditions during this period can have a serious impact on their academic condition even on their physical and mental health in adulthood. This study aims to screen mental health in students at Muhammadiyah and Aisyiyah Universities located in the Special Region of Yogyakarta.Subjects and Method: This was a cross-sectional study. A sample of 251 students of Muhammadiyah and Aisyiyah Universities in the Special Region of Yogyakarta were selected by accidental sampling. The study variable was emotional mental disorders which were measured using the Self Rating Questionnaire-20 instrument. Respondents who experienced more than seven symptoms were indicated to have a mental-emotional disorder and needed psychological help. The data were analyzed descriptively.Results: The screening results revealed that 104 students (41.43%) were experiencing mental and emotional disorders and required psychological assistance. In terms of the underlying factors of these disorders, 87.50% of students reported feeling easily fatigued (low energy), 70.19% had difficulty making decisions (cognitive), 52.88% felt unhappy (depression), 55.77% experienced abdominal discomfort (physiological), and 79.81% reported feeling nervous, tense, and worried (anxiety).Conclusion: it is recommended that schools provide accessible psychological counseling and implement stress management programs to help students cope with fatigue, anxiety, and decision-making difficulties